تہذیبی تکثیریت و آفاقیت کے سیاق میں اقبال کے تصور "وحدت آدم" کی عصری معنویت: (Contemporary significance of Iqbal's concept of Wahdat-e-Adam in the context of Civilizational Pluralism and Universality.) - محمدشفیع اللہ (Tashkeel e Jadeed, 2024)
In today's multi-civilization world, the dangers of civilization conflict are being predicted. Western thinkers have given the concept of universal civilization to remedy the civilizational conflict and misunderstanding. Under which all the civilizations of the world have to be integrated to create a common global civilization. The main purpose is to facilitate imperialism by imposing European civilization on a global level by establishing the dominant European civilization and cultural traditions on other nations. In the second option, the concept of civilizational pluralism is being given, under which all the civilizations of the world should be given full opportunity to flourish while maintaining their identity. A century ago, Iqbal, realizing the dangers of civilizational conflict and mixing, gave the concept of ‘’ Unity of Adam” In which all civilizations have opportunities to learn side by side with tolerance, respect, love and freedom, and to be created such an atmosphere of brotherhood, co-operation and unity among them that there are no dangers of violence and conflict. To solve the contemporary civilizational and cultural problems, there is an urgent need to see Iqbal's concept''Wadat-e-Adam''in the perspective of 21st century. In the light of Iqbal’s texts, a multi-civilized global society can be organized which will be based on humanistic foundations instead of the imperialist global civilizational system.